2010
DOI: 10.1248/cpb.58.811
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies on Glycosphingolipids from Protostomia Phyla: Synthesis of Glycosphingolipids from the Parasite Schistosoma mansoni

Abstract: Synthetic access to three neutral glycosphingolipids from the parasite Schistosoma mansoni adult worm has been achieved. These structures differ significantly from those of other parasites and exhibit a unique structural motif termed "schisto-core" consisting of GalNAcb b1→4Glcb b1→sequence. We have synthesized glycosphin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…To prepare the Fucα1-2Gal sequence α-stereoselectively, we selected 3,4-di-acyl protected fucosyl donor 7 [ 14 ], which was obtained from 6 [ 11 ] by benzoylation. Previous studies have indicated that 3,4-di-acyl-protected fucopyranosyl donors induce high α-selectivity in fucosylation [ 2 ]. Glycosylation of 5 with 7 in the presence of methyl trifluoromethanesulfonate (MeOTf) [ 15 ], tri- tert -butyl pyridine (TTBP) and MS AW-300 in CH 2 Cl 2 afforded desired trisaccharide ( 8 ) in 73% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare the Fucα1-2Gal sequence α-stereoselectively, we selected 3,4-di-acyl protected fucosyl donor 7 [ 14 ], which was obtained from 6 [ 11 ] by benzoylation. Previous studies have indicated that 3,4-di-acyl-protected fucopyranosyl donors induce high α-selectivity in fucosylation [ 2 ]. Glycosylation of 5 with 7 in the presence of methyl trifluoromethanesulfonate (MeOTf) [ 15 ], tri- tert -butyl pyridine (TTBP) and MS AW-300 in CH 2 Cl 2 afforded desired trisaccharide ( 8 ) in 73% yield.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our studies on unique glycoconjugates found in parasites, we have synthesized various glycosphingolipids and carbohydrate portions of glycoproteins with the aim of elucidating the mechanisms of host-parasite interactions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In previous studies we have synthesized unusual carbohydrates from the parasites Echinococcus multilocularis [ 1 , 3 , 6 ], Schistosoma mansoni [ 2 ] and porcine roundworm (nematode) Ascaris suum [ 7 ]. In this paper we describe the synthesis of the carbohydrate portion of glycoproteins from Toxocara canis and T. cati .…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our studies on natural oligosaccharides from invertebrate animal species, we are interested in the unique glycosphingolipids (GSLs) and glycoproteins (GPs) found in various Protostomia phyla and we have synthesized these oligosaccharides in order to elucidate biological functions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In particular, our interests have been focused on the unique oligosaccharide structures of GSLs and GPs found in several parasites including Echinococcus multilocularis [ 2 , 7 , 8 , 11 , 12 , 13 , 15 ], Schistosoma mansoni [ 5 , 10 ], Ascaris suum [ 1 , 17 ], and Toxocara canis [ 6 ]. Among them, GSLs and GPs from E. multilocularis have attracted our special attention.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have focused on higher animals and relatively little is known about the functions of glycoconjugates in lower animals [ 2 ]. In order to study the biological properties of glycans in glycoconjugates, over the past decade we have synthesized novel glycolipid and glycoprotein derivatives found in various invertebrates [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Organic synthesis is a powerful method to explore structure activity relationships by providing access to large amounts of homogeneous and structurally defined oligosaccharides including not only natural compounds, but also non-natural compounds [ 13 ].…”
Section: Introductionmentioning
confidence: 99%